Application of Mathematical Concepts in the Health Sector through Data Analysis Learning Using Microsoft Excel for Senior High School Students at SMA Pasundan Majalaya - Abdul Gazir Syarifudin; Rizki Apriva Hidayana; Rika Amelia; Tubagus Robby Megantara; Nenden Siti Nur Kholipah; Athaya Zahrani Irmansyah; Indah Mauludina Hasanah; Wulan Anggraeni; Ida Widiawati; Wiwin Widayani; Desi Hidayati; Anita Megawati Fajrin (Research Collaboration Community (Rescollacom), 2026)
This community service program aims to strengthen students’ numeracy, digital literacy, and health literacy through the application of mathematical concepts in health data analysis using Microsoft Excel. The activity was conducted at SMA Pasundan Majalaya and involved senior high school students as participants. The program was designed in the form of socialization and hands-on training sessions, including basic arithmetic operations, simple data analysis, logical functions, data visualization techniques, and simple regression analysis applied to health-related data. The implementation employed a participatory learning approach to support students’ understanding and engagement in the learning process. The results indicate an improvement in students’ ability to process, analyze, and interpret health data using Microsoft Excel. This program demonstrates that contextual and application-based mathematics learning can effectively enhance students’ analytical skills and awareness of the role of mathematics in real-world health contexts.